(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
The Author explores the widely debated topic of the dissemination of legal rules and decisions, applying it to the case of cooperation between Italian and Brazilian higher courts. The essay aims at evaluating whether Italian and Brazilian judges go beyond formal traditional contacts, engaging in more meaningful exchanges. The analysis of the case-law – and particularly of the Brazilian one – shows recurrent analogies suggesting a Brazilian model that, despite having many traits in common with the Italian legal tradition, is still developing its own path.